Angry Jewish Resistance. Interpreting Shylock's Rage. (2nd January 2022) - Bassi, Shaul
ABSTRACT: This essay explores different cultural protocols of representation of Jewish anger in different "emotional communities", a category proposed by historian Barbara H. Rosenwein. I examine documents from early modern Venice that provide a more nuanced comprehension of how local Jews, Shylock's historical counterparts, did feel, express and were allowed to express their anger, trying to show their relevance for the interpretation of Shakespeare's play. Taking my cue from James Shapiro's new preface for the twentieth anniversary edition of Shakespeare and the Jews, I compare the conditions of Jewish anger in the United States and Italy in reference to public and literary discourse on the Shoah and on Israel, in their intersections with criticism of The Merchant of Venice .